An assessment on cage/pen culture in the Tonle Sap Lake : case study in Siem Reap Province, Cambodia - Thak Kuntheang; Yakupitiyage, Amararatne; Yang, Yi; Bhujel, Ram C.; Sweden (Sida) (Pathum Thani, Thailand : Asian Institute of Technology, 2006)
An assessment on cage/pen culture in the Tonle Sap Lake was carried out from February to May 2006 in Choung Khneas commune, Siem Reap province, Cambodia including locating cage culture, culture designs and practices, economic performance, trash fish feed and the relationship between capture fisheries and aquaculture in order to formulate a set of recommendations for sustainable development in the future culture systems. 12 cage owners (9 cages of Pangasius sp. and 3 cages of Clarias catfish) by different cage sizes were selected as target samples. Two main types of data were used such as secondary and primary data (observation and participatory rural appraisal in aquaculture (PRA), questionnaire survey as baseline, history record data in different months during fishing and culture for cage/pen owner, monitoring checklist survey in order analyze and present the results. Chong Khneas commune is one of the floating areas where cage/pen cultures are moved up and down based on season. There were mainly 2 cultured species; Pangasius sp. and Clarias catfish. Cage sizes were divided into small cage, medium cage and big cage and were made of wood and bamboo, iron nail and string, rattan string, rope and anchors. The total cages for this year (2006) reached 67 cages (47 cage for Pangasius sp. and 20 for Clarias catfish). Availability of Pangasuis sp. seeds depended on season obtained from capture fisheries in the Tonle Sap Lake. Clarias catfish seeds received 20 % of seed from hatchery in the country but 80 % of seed were from Vietnam through middle men. The main feed is trash fish caught from the Tonle Sap Lake during the open fishing season; however, there were small amount of trash fish used for cage/pen culture for both species with rice bran and morning glory during the close fishing season. The spoiled fish remained from the open fishing season were used only for Clarias catfish species. The FCR in all cage sizes varied based on culture management, stocking fish density and feeding strategy of each cage/pen farmer. Fish mortality of Pangasius sp. occurred around April-May and higher during November due to swollen eye and wound on body disease. Clarias catfish species in cage culture had high fish mortality at the start of stocking and about 30 % during rainy season caused by wound on fish body disease. Market activities were at the farms, local commune markets, and provincial markets. Fish market sizes were larger than 1.2 kg/fish for Pangasius sp and from 0.4-0.7 kg/fish for Clarias catfish species. Economically, used of big cages for both species gave higher net returns than small and middle cage due to lower operation cost especially trash fish feed cost. Problems facing by both species cage farmers were shortage of Pangasius sp. seed, shortage of trash fish feed, low income from cage/pen culture production and shortage of techniques/extension knowledge and transfer. A total 20 fish species were used as fish feed, for sale, human consumption or processing. There were a total 17 trash fish species of which 6 major species were found in trash fish feed in cage culture system form February-April. At present, cage/pen culture systems do not have much impact on the environment besides a little bit of water pollution and effects of eutrophication
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Aquaculture and Aquatic Resources Management, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2006
Keywords: Cage aquaculture -- Cambodia -- Tonle Sap (Cambodia : Lake)